The Bakhshālī Manuscript: A Response to the Bodleian Library's Radiocarbon Dating - Plofker, Kim; Keller, Agathe; Hayashi, Takao; Montelle, Clemency; Wujastyk, Dominik (History of Science in South Asia, 2017)
Popular attention has recently been captured by the results of the Bodleian Library's 2017 project of radiocarbon datingportions of the birch-bark fragments constituting what is known as the Bakhshālī Manuscript.  In this paper, we disagree with the interpretation of the findings announced by the Bodleian team. In particular, we argue that the earliest dated folio of this manuscript is unlikely to be the date of the whole text. Rather, the latest dateable folio is logically the date of the scribal activity. This fits well with past estimates of the date of the Bakhshālī Manuscript based on historical, philological and palaeographic arguments..  And we argue that the Bakhshālī Manuscript does include written zeros that function as arithmetical operators, i.e., as numbers in their own right, and not merely as place-holders, as asserted by the Bodleian team. Finally, we express regret that the Bodleian Library chose to announce scientific results without peer-review and through a press release to newspapers and a YouTube video.